Tensile behaviour of isotactic polypropylene with different crystallinities and service temperatures. (December 2022) - Ma, Haowei; Li, Taidong; Pan, Baisong; Li, Jiquan; Jiang, Shaofei; Peng, Xiang; Jing, Liting
Abstract: Isotactic polypropylene (iPP) has been increasingly used owing to its advantages. However, the variation in crystallinity and service temperature of this material will affect its mechanical behaviour significantly, resulting in a lightweight material and an unreliable fatigue resistance prediction. In this study, a prediction model was established for the tensile behaviour, crystallinity, and service temperature of iPP. The model was composed of three parameter functions established separately based on three stress-strain stages. The undetermined material constants of the model were obtained by fitting the tensile experimental data under different crystallinities and service temperatures. Additionally, a control group of the tensile experiment was conducted under different conditions, and the predicted values were compared with the stress results of the control experiment to verify the accuracy of the prediction model. The results showed that the fitted R -square values were all greater than 0.91 for the undetermined material constants, and the maximum error between the experimental and predicted data was 9.58%. The model provides a quantitative prediction method for the tensile behaviour of iPP considering both crystallinity and service temperature, achieving both a lightweight material and fatigue resistance prediction of iPP. Highlights: A prediction model was established for the tensile behaviour, crystallinity, and service temperature of iPP. The crystallinity of the samples was increased by annealing temperature improvement significantly. The yield stress and elastic modulus decreased with increasing service temperature significantly. When the service temperature is close to the glass transition temperature, the strain-softening phenomena are inconspicuous. The effects of crystallinity and service temperature on tensile behaviour should be considered comprehensively for iPP.